The Effectiveness of Traditional Chinese Medicine Jinlida Granules on Glycemic Variability in Newly Diagnosed Type 2 Diabetes: A Double-Blinded, Randomized Trial - Jiemin Pan; Yuejie Xu; Si Chen; Yinfang Tu; Yifei Mo; Fei Gao; Jian Zhou; Cheng Hu; Weiping Jia (Journal of Diabetes Research)
This study aimed to evaluate the influence of Jinlida granules on glycemic variability with or without metformin treatment in patients with newly diagnosed type 2 diabetes. This study was a 16-week, double-blinded, randomized, controlled clinical trial. The enrolled patients with newly diagnosed type 2 diabetes were randomly divided into four groups: control, Jinlida, metformin, and combination treatment groups. A retrospective continuous glucose monitoring (CGM) system was used for subcutaneous interstitial glucose monitoring for 3 days consecutively. Hemoglobin A1c (HbA1c), traditional Chinese medicine symptom score, and CGM parameters, including glucose coefficient of variation, standard deviation of blood glucose values, and time in range of glucose 3.9–10.0 mmol/L, were assessed pre-test and post-test. A total of 138 participants completed the entire procedure. Compared with the pre-test, fasting plasma glucose, 2 hour postprandial plasma glucose, HbA1c, and traditional Chinese medicine symptom score all decreased in the four groups at the end of the test, and the combination treatment group showed the most significant decrease. In terms of CGM parameters, time in range of the Jinlida and metformin groups improved after intervention compared with the baseline (Jinlida group: 78.68 ± 26.15 versus 55.47 ± 33.29; metformin group: 87.29 ± 12.21 vs. 75.44 ± 25.42; P < 0.01). Additionally, only the Jinlida group showed decreased glucose standard deviation after intervention (1.57 ± 0.61 vs. 1.96 ± 0.95; P < 0.01). Jinlida granules can improve glycemic control and glycemic variability in patients with newly diagnosed type 2 diabetes. Clinical trial registration number: ChiCTR-IOR-16009296.